Performance Analysis of Different Control Strategies in a Z-source Inverter - Nayak, B.; Dash, S. S. (Engineering, Technology & Applied Science Research, 2013)
This paper presents the analysis for different control techniques in Z-source inverters. The voltage gain versus modulation index from simulation result is compared with the mathematical calculated voltage gain. Further detailed analysis of %THD, %harmonics of output voltage at different modulation indexes for different boosting techniques of a Z-source inverter are also performed with respect to the traditional VSI by MATLAB based simulation